Does engaging in creative activities influence the use of coping skills and perception of challenge-skill balance in elite athletes? - Richard, V.; Yang, Y.; Runco, M.; Abdulla, A. M.; Tenenbaum, G. (Journal of Psychology & the Behavioral Sciences, 2019)
The aim of this study was to test the notion that engagement in creative activity directly affects the flow state dimension of challenge-skills balance, and indirectly via coping strategies in the realm of sport. Two hundred and eight athletes classified as intermediate, advanced, and expert level were administered a Creative Activities and Accomplishment Checklist (CAAC), the Dispositional Coping Inventory for Competitive Sport (DCICS), and the Challenge-Skill Balance subscale of the Dispositional Flow Scale (CS-DFS-2). Measurement and structural equation modeling were used to test the postulated model. The best fit of the model showed that 36% of the variance in challenge-skills balance was accounted for by creative activities and task-oriented coping, of which 27% was attributed to the indirect effect from creative activities via task-oriented coping. The findings extend the role that creativity engagement has on flow state.